2002
DOI: 10.1108/01437720210453885
|View full text |Cite
|
Sign up to set email alerts
|

Ethical attitudes and ethical behavior: are managers role models?

Abstract: Ethical attitudes and ethical behavior in organizations may have substantial ramifications on a firm's operation. This study investigates whether or not managers are perceived by employees to exhibit ethical attitudes and ethical behavior and thereby being their role models. A sample of 111 employees within the finance department of a major municipality who are exposed to unethical behavior responded to a structured questionnaire concerning ethical and unethical episodes. There were three major findings: first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 30 publications
5
24
0
2
Order By: Relevance
“…Business ethics related studies cover an array of issues, including macro environmental issues (Singh and Carasco, 1996), human rights principle (Cragg, 2000), industry-specific practices (Lamb, 1999), organizational philosophy (Hunt et al, 1989), and individual conducts (Kantor and Weisberg, 2002;Lund, 2000). Business ethics has been widely studied in the areas of marketing, information management, labor relations, and human resource management.…”
Section: Introductionmentioning
confidence: 99%
“…Business ethics related studies cover an array of issues, including macro environmental issues (Singh and Carasco, 1996), human rights principle (Cragg, 2000), industry-specific practices (Lamb, 1999), organizational philosophy (Hunt et al, 1989), and individual conducts (Kantor and Weisberg, 2002;Lund, 2000). Business ethics has been widely studied in the areas of marketing, information management, labor relations, and human resource management.…”
Section: Introductionmentioning
confidence: 99%
“…As such, it can be argued that EA will significantly influence whether or not a manager would engage in DB, or likewise, how one behaves may actually mirror their EA. Prior researchers (like Ferrell, & Weaver, 1978;Izraeli, 1988;Kantor, & Weisberg, 2002) suggested that employees could be more ethical in some behavioural situations than in others and different situations may lead to different ethical perceptions. Employees exhibited strong ethical attitude against the perceived most unethical actions that clearly may hurt another person or damage the organization, but were much simpler to rationalize and justified the slightly unethical acts.…”
Section: Ethical Attitude (Ea)mentioning
confidence: 99%
“…Under personal ethics, ethical attitudes (EA) has been suggested as the best predictor of employees' unethical behaviour (Izraeli, 1988) and has attracted a profound concern as evidenced by the large number of studies published (like Ghosh, & Crain, 1995;Izraeli, 1988;Kantor, & Weisberg, 2002;Longenecker, McKinney, & Moore, 2003;Longenecker, Moore, Petty, Palich, & McKinney, 2006;Medlin, & Green, 2003;Reckers, Sanders, & Roark, 1994;Wong, 2008;Zabid, & Alsagoff, 1993). EA refers to the perceived rightness or wrongness of a situation which might reflect a favourable, unfavourable, or neutral view, and subsequently affect one's decision whether to commit a behaviour (Kantor, & Weisberg, 2002).…”
Section: Ethical Attitude (Ea)mentioning
confidence: 99%
See 2 more Smart Citations